Developing a research agenda for maternal health in the Top End of the Northern Territory of Australia: a participatory approach - Emily R. Bowden; Kiarna Brown; Marissa Smiler-Cairns; Jessica Murray; Meaghan Kennedy; Gabrielle B. McCallum; Holger W. Unger (BMC Health Services Research)
Abstract Background Evidence supports that engaging consumers in developing and co-designing research priorities and protocols with key stakeholders improves acceptability of and participation in research and leads to better health outcomes. This is particularly relevant when considering research with First Nations, migrant and refugee populations, adolescents, women living with disability and those in the LGBTQIA + community who face systemic disadvantage, shouldering a disproportionate burden of poor outcomes. This study aimed to identify priorities for maternal health research in the Top End of the NT from the perspective of consumers and key stakeholders. Methods Using a participatory approach, focus groups and in-depth discussions with consumers, maternal health care providers and stakeholders were conducted over a three-month period (Part A), followed by a 1-day stakeholder forum in Darwin (Part B). Data was triangulated and a list of research priorities developed. Results Five priorities emerged. First, there is a need to develop and test strategies removing barriers for engagement of consumers and clinicians in maternal health research. Second, research into specific clinical concerns raised by consumers, such as prevention of preterm birth, must be complemented by health systems research enabling better patient journeys. Third, there is a need to develop and test innovative tools to enable comprehensive counselling of women from diverse backgrounds regarding aspects of care, based on most recent evidence-based and consumer needs. Further, there is a demand for research into innovative approaches to recruitment and retention of maternity care providers in a sparsely populated region of Australia, with a focus on provider well-being and continuity of integrated care. Finally, a need for research collaboration across similar settings and relevant disciplines to enable enhanced maternal health was identified. Conclusions Emerging research priorities, implementing evidence-based practices, and regularly updating these priorities through ongoing stakeholder engagement, can work towards a future where maternal health services are accessible and responsive to the diverse needs of women and families residing in the Top End of the NT. Whilst consumers and stakeholders raised specific clinical priorities, health system research was identified as a key priority, focussing on patient journeys, co-design, and continuity of care through staff retention.